Założenie obronne w Czarnym Sadzie, stan. 1, gm. Koźmin, woj. kaliskie w świetle badań terenowych w 1987 roku - Wojda, Leszek (Acta Universitatis Lodziensis. Folia Archaeologica, 1992)
The programme of verifying earthworks in Great Poland is being continued by the Centre for the Archaeology of Great Poland of the Institute for History of Material Culture, Polish Academy of Sciences, in cooperation with Provincial Conservators of Monuments. After initial verification the Kalisz province is now being investigated for earthworks by means of sounding and boring works. Verification and sounding of a feature at Czarny Sad are part of the programme. The feature is known in relevant literature as an early medieval ring-shaped earthwork, roughly dated to phase D, yet not excavated so far. The earthwork is circular in shape. 60 m or so across, with the rampart still standing to a height of 3-4 m, and is surrounded by a moat 8-10 m wide. An excavation trench, 10x2.5 m in size, was located along the N-S axis running from the top of the rampart to the enclosed space. About 487.5 m3 of the overlay and cultural layers have been explored yielding 362 potsherds, 34 pot-shaped tile fragments, a fragmentary horseshoe, fragment of a knife-handle and animal bones. The excavations revealed two phases of occupation: the first phase datable to 950-1050 is associated with the rampart of crossed logs build and with the lowest usage level of the enclosed space. The second phase should be assigned to the 15th-17th centuries and linked with the presence of a brick(?) manor-house which was probably built after the reshaping of the earthwork, indicated by the surviving levelling layers.